Pemetaan Situasi Lingkungan dengan Total Station di Kampus Universitas Pendidikan Ganesha di Jinengdalem - I Gusti Putu Adi Susila; I Gst Ngr Yoga Jayantara (Universitas Pendidikan Ganesha, 2023)
The land surface is part of the space whose existence is limited, therefore it is necessary to use the land surface in a planned and controlled manner. Judging from this, a situation mapping will be carried out which includes measuring Infrastructure and Topography Measurements in the Ganesha Education University campus environment in Bali Province, Buleleng District, Buleleng Regency. more detailed mapping will require more sophisticated technology, namely mapping using a Total Station (TS) tool. The purpose of this study is to map the UNDIKSHA campus environment in Jinengdalem Village with the resulting output in the form of a situation map and to find out how the process of making a new bm uses RTK. The method in this study is the data collection carried out in this study, namely by making direct measurements in the field using a TS tool with a closed polygon terrestrial measurement method. The results of this study are in the form of a map of the environmental situation, a topographic map, and the results of the accuracy calculation correction